Innovative Development of Guided Inquiry-Based Science Learning Materials to Improve Critical Thinking Skills among Junior High School Students - Yudha Irhasyuarna; Fahmi; Hery Fajeriadi; Muhammad Kusasi (Postgraduate, University of Mataram, 2025)
This study aims to develop guided inquiry-based science learning tools to enhance the critical thinking skills of junior high school students on the topic of additive and addictive substances. The research employed a development method using Tessmer’s formative evaluation model, which includes the stages of validation, practicality testing, and effectiveness testing. The developed learning tools consist of lesson plans (RPP), student worksheets (LKPD), and instructional materials. Expert validation results indicated that the tools are in the